Analisis Distribusi Hujan Jam-Jaman di Sub DAS Sungai Mess - Hermawan, Chitra; Dermana, Iwayan; Harmiyati, Harmiyati (JURNAL RISET INOVASI DAERAH, 2024)
Sub watershed Sungai Mess is one sub watershed which empties into the Sungai Singingi. Changes in global climate affect rainfall patterns change, in the scale of space, time, and scale. The purpose of this study is to determine the validity of rainfall existing data, to investigate the characteristics of rainfall, to determine the distribution pattern of hourly rainfall in the Kuantan sub watershed. The validity of rainfall data was conducted by RAPS (Rescaled Adjusted Partial sums). The rainfall characteristics were determined by grouping data based on the duration and occurrence of rainfall. Analysis of distribution pattern of hourly rainfall was based on observed data and finded the similiarity with Mononobe Modified method, Alternating Block Method (ABM), and Triangular Hyetograph Method (THM). The analysis resulted in the validity of eight rain stations from the existing nine stations. Rainfall in the Keduang sub watershed was dominated by two-hour rainfall events. Pattern of rainfall distribution hourly showed that rainfall distribution in 2, 3, 5, 7, and 8 hours follows Modified Mononobe model, while the pattern of rainfall distribution in 4 and 6 hours follows Triangular Hyetograph Method (THM) model.